Sjuksköterskors upplevelser av arbetsrelaterade påfrestningar och hur dessa hanterades - Fischlein,Felicia; Lindell,Nina (2025)
Background: Emergency care is characterized by high workload, time constraints, and limited resources, which create a tense work environment for nurses. The Job Demand–Control–Support model describes how the combination of job demands, control, and social support affects balance or imbalance, while coping and resilience are recovery abilities that influence the nurse’s capacity to handle stressors. Aim: To explore nurses’ experiences of work-related stressors and how these were managed within emergency care. Method: A systematic literature review of qualitative studies was conducted. Searches were performed in the PubMed and CINAHL databases using the PEO model as a framework. The eleven included articles were analyzed through a descriptive metasynthesis. Results: The study was based on eleven scientific articles. Two overarching main themes were identified—Stressors and Coping—along with seven subthemes: Work environment, Unreasonable demands, Emotional regulation, Avoidant coping, and Adaptation. Conclusion: The results showed that high demands, low control, and lack of support increased the risk of stress and ill health among emergency nurses, while social support and participation could reduce stress and strengthen a sense of control. Future research should explore how leadership and work routines can enhance resilience and coping strategies to create sustainable work environments in the long term.
Keywords: Hög arbetsbelastning; akutsjukvård; hantering; påfrestningar; sjuksköterska